1962
DOI: 10.3382/ps.0411401
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus in the Nutrition of the Adult Hen

Abstract: T HE phosphorus requirement of the laying hen has been studied by many research workers during" the last thirty years. Results reported during the period 1933 to 1953 appeared to indicate a higher requirement than suggested by several more recent reports, and these apparently divergent findings have stimulated additional research at a number of experiment stations. Because of the divergent results, it appeared desirable to review details of both experimental procedures and diet composition in recent and older … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
11
1

Year Published

1969
1969
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 15 publications
1
11
1
Order By: Relevance
“…The lowest dietary phosphorus level depressed egg production at all calcium levels but this depression was most severe at the highest calcium levels. Many workers including Singsen et al (1962) have also reported a reduction in egg production with total phosphorus levels less than 0.6%. The greater depression in egg production in hens receiving 4.75% calcium and 0.35% phosphorus was probably due to the effect of the high calcium level depressing the utilization of The egg specific gravity decreased as compared to pretest values but the decrease was less marked with the higher levels of calcium.…”
Section: Methodsmentioning
confidence: 93%
“…The lowest dietary phosphorus level depressed egg production at all calcium levels but this depression was most severe at the highest calcium levels. Many workers including Singsen et al (1962) have also reported a reduction in egg production with total phosphorus levels less than 0.6%. The greater depression in egg production in hens receiving 4.75% calcium and 0.35% phosphorus was probably due to the effect of the high calcium level depressing the utilization of The egg specific gravity decreased as compared to pretest values but the decrease was less marked with the higher levels of calcium.…”
Section: Methodsmentioning
confidence: 93%
“…For the laying hen phosphorus from plant origin is usually considered to be around 50% available. However, from a review of the work of Singsen et al (1962), Temperton and Cassidy (1964), Waldroup et al (1965Waldroup et al ( , 1967 and Nelson (1967) it is apparent that there are a number of factors influencing the availability of plant phosphorus and that there is lack of agreement as to how much can be utilized by poultry.The present work was undertaken to study the influence of steam pelleting on the utilization of phytin phosphorus by the laying hen. At the same time an attempt was made to gain information on the value of phytin or plant phosphorus in meeting the laying hens requirement for egg production purposes.…”
mentioning
confidence: 94%
“…For the laying hen phosphorus from plant origin is usually considered to be around 50% available. However, from a review of the work of Singsen et al (1962), Temperton and Cassidy (1964), Waldroup et al (1965Waldroup et al ( , 1967 and Nelson (1967) it is apparent that there are a number of factors influencing the availability of plant phosphorus and that there is lack of agreement as to how much can be utilized by poultry.…”
mentioning
confidence: 94%
“…The simplified low phosphorus basal ration (0.20% total P) was the same as previously described by Singsen et al (1962), with the exception of the addition of 0.05% DL-methionine to the ration. In experiment 1, each replicate consisted of 15 range-reared Darby S.C. White Leghorn pullets housed in individual 11"X18" cages.…”
Section: Methodsmentioning
confidence: 99%